Pathways to social development: Rosa Luxemburg's studies on the anthropology and sociology of imperialism. Issue 1 (2nd January 2023) - Hudis, Peter
ABSTRACT : While Rosa Luxemburg is widely known for her critique of reformism and political authoritarianism, less attention has been paid to her anthropological and ethnographic studies of non-Western and precapitalist societies. This chapter examines Luxemburg's work on this in her Introduction to Political Economy and writings composed between 1907 and 1914 at the school of the German Social-Democratic Party in Berlin. In doing so, it compares and contrasts Luxemburg's studies on the non-Western world with the late writing of Marx (1872–1883), especially concerning "the so-called primitive accumulation of capital."